Volume 2: Fora 2009
DOI: 10.1115/fedsm2009-78507
|View full text |Cite
|
Sign up to set email alerts
|

Numerical and Experimental Analyses for the Aerodynamic Design of High Performance Counter-Rotating Axial Flow Fans

Abstract: A study was done on the numerical and experimental analyses for the aerodynamic design of high performance of the counter rotating axial fan (CRF). Front rotor and rear rotor blades of a counter rotating axial fan are designed using the simplified meridional flow analysis method with the radial equilibrium equation and the free vortex design condition, according to design requirements. The through-flow fields and the aerodynamic characteristics of the designed rotor blades are analyzed by the matrix method and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Few pieces of research are reported in open literature concerning performance study of counter-rotating fan stage. Cho et al [1] showed that in the case of contra-rotating fan the efficiency is at its peak when the hub-to-tip ratio is 0.4, which is almost the same point for front and rear rotor maximum efficiency. Further, they have also established that the static pressure rise is higher at tip regions of the front rotor and hub regions of the rear-rotor blade considering the variation of the relative velocity.…”
Section: Introductionmentioning
confidence: 88%
“…Few pieces of research are reported in open literature concerning performance study of counter-rotating fan stage. Cho et al [1] showed that in the case of contra-rotating fan the efficiency is at its peak when the hub-to-tip ratio is 0.4, which is almost the same point for front and rear rotor maximum efficiency. Further, they have also established that the static pressure rise is higher at tip regions of the front rotor and hub regions of the rear-rotor blade considering the variation of the relative velocity.…”
Section: Introductionmentioning
confidence: 88%
“…Among the few studies dedicated to the design procedure of a counter-rotating stage one can cite the works of Cho et al [14] who use a conventional design method based on the simplified meridional flow method with the radial equilibrium equation and the free vortex design con-dition, and study the effect of parameters such as the hub to tip ratio, or the solidity. Cao et al [15] used Computational Fluid Dynamics results to re-design the rear rotor of a counter-rotating pump and obtain an increase in performances with respect to the original rear rotor conventional design.…”
Section: Introductionmentioning
confidence: 99%
“…The results showed larger pressure rise and efficiency with lower rotation rate at a given power consumption. Cho et al 4 showed how to design rotor blades and Wang et al 5 investigated different blade pitch angles to validate and improve recommendations for shaft power matching of CRFs. Another focus has been on the reduction of sound emission, see Shin et al 6 and Li et al 7 Grasso et al 8,9 focused on the reduction of the mechanical stresses and broadband noise scattered from the trailing-edge of the blades.…”
Section: Introductionmentioning
confidence: 99%